2013
DOI: 10.1109/tdmr.2013.2258672
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Snapback Model by Transient I-V Measurement for Circuit Simulation of ESD Response

Abstract: It is demonstrated that if the compact model of a snapback-type device is calibrated using only pulsed I-V data, it may not correctly reproduce the device response to arbitrary electrostatic discharge (ESD) waveforms. Transient I-V measurements are demonstrated to improve the completeness of the device characterization and model verification. Given an accurately calibrated ESD compact model, circuit simulations may be used to identify device-tester interactions that have been reported to cause unexpected damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Meng and Rosenbaum [73] demonstrated that a MOSFET model composed of the PDK model and an ESD wrapper can perform very well in diverse ESD simulations. The model replicates the "snap-up" that occurs if a significant amount of charge remains on the capacitances inside an ESD tester when the protection device turns off; this is shown in Fig.…”
Section: N-channel Mosfetmentioning
confidence: 99%
See 1 more Smart Citation
“…Meng and Rosenbaum [73] demonstrated that a MOSFET model composed of the PDK model and an ESD wrapper can perform very well in diverse ESD simulations. The model replicates the "snap-up" that occurs if a significant amount of charge remains on the capacitances inside an ESD tester when the protection device turns off; this is shown in Fig.…”
Section: N-channel Mosfetmentioning
confidence: 99%
“…The model replicates the "snap-up" that occurs if a significant amount of charge remains on the capacitances inside an ESD tester when the protection device turns off; this is shown in Fig. 23 [73]. The model was used to study a related phenomenon-the retriggering and oscillations that may occur during the tail end of an HBM test and that can damage the DUT.…”
Section: N-channel Mosfetmentioning
confidence: 99%
“…Previous works have addressed parameter extraction for the finger model [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. This work focuses on the extraction of the model parameters for the body resistance network.…”
Section: Model Parameter Extractionmentioning
confidence: 99%
“…Transistors exposed to ESD include those used in I/O circuits and active rail clamp circuits. Many ESDrelevant models for MOSFETs may be found in the open literature, e.g., [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The majority of these works treat the body resistance as a single element, in effect representing the device as a single-finger MOSFET.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation